"Great Grandfather Wm. Willis Bemister" - Rorke Family (1840)
William Willis Bemister. William Willis Bemister (1789-1863), second son of John Bemister and Mary (Willis) Bemister, was born at Corfe Mullen, Dorsetshire, England on 7 May 1789. He came to Newfoundland in 1803 as a clerk with the firm of George & James Kemp. He married Ann Howell at Carbonear on 25 November 1810 and had 9 children including Mary (Bemister) Forward (wife of Capt. Mark Forward), William, Hon. John, Capt. Willis and Sarah Jane (Bemister) Pike. He later operated the firm of W. Bemister & Co. at Carbonear. He died at Carbonear on 30 December 1863. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.